Photorealistic imaging of left atrial appendage occlusion/exclusion. Issue 8 (5th August 2019) - Vainrib, Alan F.; Bamira, Daniel; Aizer, Anthony; Chinitz, Larry A.; Loulmet, Didier; Benenstein, Ricardo J.; Saric, Muhamed
Abstract: Recent improvements in 3D TEE post processing rendering techniques referred to as TrueVue (Philips Medical Systems, Andover, MA, USA). It allows for novel photorealistic imaging of cardiac structures including left atrial appendage (LAA) and its closure devices. Here we present TrueVue images of the LAA prior to and after LAA exclusion/occlusion using various percutaneous and surgical techniques. TrueVue may improve delineation of LAA anatomy prior to occlusion as well as visualization of occluder device position within the LAA.